1999
DOI: 10.1021/jo990346w
|View full text |Cite
|
Sign up to set email alerts
|

Structure Determination and Electrochemistry of Products from the Radical Reaction of C60 with Azo(bisisobutyronitrile)

Abstract: Thermal decomposition of azo(bisisobutyronitrile) in a 1,2-dichlorobenzene solution of C60 gave three regioisomeric 1,x-di(2-cyano-2-propyl)-1,x-dihydro[60]fullerenes in 12, 2, and 4% yields, assigned as the 1,4-, 1,2-, and a third isomer of still uncertain structure. The 1,4- and unidentified isomers underwent three reversible reduction steps by cyclic voltammetry, and UV−vis−NIR spectra of the mono- and dianions generated electrochemically were recorded. The first two redox potentials of the 1,4-isomer were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 38 publications
1
40
0
1
Order By: Relevance
“…Here, we present the radical functionalization of singlewalled carbon nanotubes with AIBN in a 1,2-dichlorobenzene (oDCB) solution, which has emerged from the pioneering work with fullerenes by Ford et al [12,13]. The studies have shown that radial species of AIBN can efficiently couple to the surface of C 60 , resulting in highly functionalized fullerenes.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we present the radical functionalization of singlewalled carbon nanotubes with AIBN in a 1,2-dichlorobenzene (oDCB) solution, which has emerged from the pioneering work with fullerenes by Ford et al [12,13]. The studies have shown that radial species of AIBN can efficiently couple to the surface of C 60 , resulting in highly functionalized fullerenes.…”
Section: Introductionmentioning
confidence: 99%
“…Compound 1 (0.05 g) was obtained as dark brown powder, whose individual character was confirmed by the con sistency between the spectral characteristics obtained by 1 H and 13 C NMR spectroscopy and by electronic spectroscopy and the published data. 11 Since fullerene and its derivatives are prone to incomplete combustion during elemental analysis, 2 the compo sitions of the compounds synthesized were confirmed by the weight loss data of thermogravimetric and thermal decomposi tion studies and by the compositions of the volatiles and the solid residue of the decomposition. The weight loss of sample 1 on heating to 673 K is due to the detachment of the [CMe 2 CN] fragments from fullerene, which remained in the solid residue.…”
Section: Methodsmentioning
confidence: 94%
“…Substance 1 was synthesized by a modified procedure. 11 The synthesis temperature was increased from 348 to 398 K in order to increase the content of 1,4 di(2 cyanoisopropyl) 1,4 dihy drofullerene, which should be more stable than 1,2 di(2 cy anoisopropyl) 1,4 dihydrofullerene. o Dichlorobenzene, a sol vent of relatively high polarity for chromatography, was removed in vacuo after the synthesis.…”
Section: Methodsmentioning
confidence: 99%
“…¦ÅÑ ÓÇÛÇÐËÇ ÔÑÑÕÄÇÕÔÕÄÖÇÕ àÍÔÒÑÐÇÐÙËÂÎßÐÑÏÖ ÊÂÕÖØÂ-ÐËá ËÊÎÖÚÇÐËâ: [56], ÒÑÍÂÊÞÄÂáÕ, ÚÕÑ ËÑÐËÊÂÙËâ àÕËØ ÍÎÂÔÕÇÓÑÄ ÏÑÉÇÕ ËÏÇÕß ÏÇÔÕÑ ÍÂÍ ÄÔÎÇAEÔÕÄËÇ ÏÇØÂÐËÊÏ "ÊÂÉËÅÂÐËâ", ÕÂÍ Ë Ä ÓÂÏÍÂØ ÏÑAEÇÎË ÍÑÅÇÓÇÐÕÐÑÅÑ àÎÇÍÕÓÑÐÐÑÅÑ AEÄËÉÇÐËâ [11].…”
Section: £äçAeçï ðñäöá ×öðíùëáunclassified